Inhibition of BTF3 sensitizes luminal breast cancer cells to PI3Kα inhibition through the transcriptional regulation of ERα. (January 2019) - Ding, Jinlei; Wang, Xiaonan; Zhang, Yuan; Sang, Xiaolin; Yi, Jingyan; Liu, Chongya; Liu, Zundong; Wang, Min; Zhang, Nan; Xue, Yijue; Shen, Lanlin; Zhao, Wenzhi; et al.
Abstract: Selective phosphatidylinositol 3 kinase (PI3K) inhibitors are being actively tested in clinical trials for ERα-positive (ER+) breast cancer due to the presence of activating PIK3CA mutations. However, recent studies have revealed that increased ERα transcriptional activity limits the efficacy of PI3K inhibitor monotherapy for ER + breast cancers. Herein, we report the identification of BTF3 as an oncogenic transcription factor that regulates ERα expression in luminal breast cancers. Our TCGA analysis reveals high expression levels of BTF3 in luminal/ER + breast cancer and cell line models harboring ERα overexpression. Concordantly, BTF3 expression is highly and strongly associated with ESR1 expression in multiple breast cancer cohorts. We further show that BTF3 promotes the proliferation, survival and migration of ER + breast cancer cells by modulating ESR1 expression and ERα-dependent transcription. Moreover, BTF3 knockdown sensitizes ER + breast cancer cells to the PI3Kα inhibitor BYL-719 in both in vitro and in vivo models. Together, our findings highlight a novel role of BTF3 in modulation of ERα-dependent transcriptional activity and its potential as a predictive marker for the response to PI3K-targeted therapy in ER + breast cancer. Highlights: High expression levels of BTF3 exist in luminal/ER + breast cancer. BTF3 promotes the proliferation, survival and migration of ER + breast cancer cells. BTF3 regulates ESR1 expression and ERα-dependent transcription. BTF3 knockdown abrogates the upregulation of ERα expression induced by BYL-719. BTF3 silencing sensitizes ER + breast cancer cells to BYL-719 in vitro and in vivo .